Economic Implications on the Composition of Municipal Solid Waste and its Management in Kota City - Dr. Shweta Mathur (International Journal of Engineering and Management Research, 2018)
An appropriate technology for waste management in developing countries not only reflects the concern over the operation and cost of machines imported from developed countries but also entails the social and environmental goals of sustainable development based on techniques appropriate to specific settings. In connection with much of the published data, the information is of only partial benefit to a designer or planner, since the national averages presented are applicable only very broadly to the entire nation; that is, to adequately design a solid waste management system for a particular locality comprehensive information about the solid waste in that locality must be obtained. Since solid waste reflect the life-style of the generating populace, the character and amounts of various components in the solid waste stream will vary from locale to locale in Kota city. This paper presents the findings of a study carried out in economically different localities in Kota city to determine the solid waste composition based on field surveys and its management.